Alkaline dry cell batteries
By adding a specific molar ratio of P-O-bonded compound A and terephthalic acid to the negative electrode of an alkali dry battery, the problem of poor balance of the electrolyte in a low-temperature environment is solved, and the discharge performance is significantly improved.
Patent Information
- Application Number
- CN202080093698.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-29
- Filing Date
- 2020-10-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-10-20
AI Technical Summary
In low temperature environments, the discharge performance of alkaline dry batteries decreases, mainly due to the poor balance between the negative electrode and the positive electrode, which makes the electrolyte difficult to diffuse and affects the discharge performance.
Compound A with P-O bond and terephthalic acid were added to the negative electrode of the alkali dry battery, and the molar ratio of Compound A was 0.025 or more and 2.5 or less to improve the balance and diffusion of the electrolyte.
Through the specific molar ratio, the discharge performance of alkaline dry batteries in low-temperature environments is significantly improved, the balance and conductivity of the electrolyte are ensured, and the low-temperature performance of the battery is improved.
Smart Images

Figure CN114982000B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to improvement of discharge performance of alkaline dry batteries in a low-temperature environment. Background Art
[0002] Alkaline dry batteries (alkaline manganese dry batteries) have a larger capacity than manganese dry batteries and can draw a large current, so they are widely used. The electrolyte of alkaline dry batteries uses an aqueous solution of potassium hydroxide, etc., which has good viscosity and ion conductivity at room temperature around 20°C.
[0003] Therefore, Patent Document 1 proposes to include phosphoric acid or phosphoric acid ions in a gelled negative electrode containing a zinc alloy containing aluminum as a negative electrode active material in order to suppress internal short circuits caused by crystal growth of reaction products during discharge.
[0004] Patent Document 2 proposes to include terephthalic acid having a specific particle size in a gelled negative electrode for the purpose of suppressing internal short circuits caused by scattering of the gelled negative electrode to the positive electrode when a strong impact is applied to the battery.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 2609609
[0008] Patent Document 2: International Publication No. 2018 / 066204 Pamphlet Summary of the invention
[0009] During discharge in a low temperature environment such as 0°C, it becomes difficult for the electrolyte (water) to move (diffuse) from the negative electrode to the positive electrode, and the balance of the electrolyte (water) between the positive and negative electrodes deteriorates, and the discharge performance sometimes decreases. During discharge, water is generated at the negative electrode and consumed at the positive electrode. Therefore, the movement (diffusion) of the electrolyte (water) from the negative electrode to the positive electrode during discharge has a great influence on the discharge performance.
[0010] One aspect of the present disclosure relates to an alkaline dry battery comprising: a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode contains: a negative electrode active material containing zinc, a compound A having a PO bond, and terephthalic acid, wherein the molar ratio of the compound A to the terephthalic acid is greater than or equal to 0.025 and less than or equal to 2.5.
[0011] According to the present disclosure, it is possible to provide an alkaline dry battery having excellent discharge performance in a low-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1This is a front view showing a part of the alkaline dry battery in one embodiment of the present disclosure as a cross section. DETAILED DESCRIPTION
[0013] The alkaline dry battery of the embodiment of the present disclosure comprises: a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. The negative electrode contains: a negative electrode active material containing zinc, a compound A having a PO bond (hereinafter also referred to as compound A), and terephthalic acid, wherein the molar ratio of compound A to terephthalic acid is 0.025 or more and 2.5 or less.
[0014] The negative electrode contains compound A and terephthalic acid in a specific molar ratio, thereby specifically improving the discharge performance in a low temperature environment. The detailed reason is unclear, but it is speculated as follows: compound A and terephthalic acid are easily mixed evenly. When compound A and terephthalic acid are mixed in a specific molar ratio in the negative electrode, the balance of the electrolyte (water) between the positive and negative electrodes during low-temperature discharge is improved. The molar ratio of compound A to terephthalic acid is preferably 0.25 or more and 2.3 or less, and more preferably 0.25 or more and 1.5 or less.
[0015] The molar ratio of compound A to terephthalic acid can be determined, for example, by the following method.
[0016] The battery is decomposed, the negative electrode is taken out, the components in the negative electrode are extracted in pure water and left to stand to obtain a supernatant, and the alkaline components in the liquid are removed by a cation removal column. After that, the amount of terephthalic acid ions in the supernatant is determined by ion chromatography (IC). In addition, the amount of phosphorus in the supernatant is determined by high-frequency inductively coupled plasma (ICP) emission spectrophotometry. The structure (molecular weight) of compound A is determined by combining liquid chromatography mass spectrometry (LC / MS) and nuclear magnetic resonance (NMR) to confirm that phosphorus originates from compound A. Based on the results of the above analysis, the molar ratio of (compound A / terephthalic acid) is determined using the obtained terephthalic acid ion amount and phosphorus amount.
[0017] In the negative electrode, the molar ratio P / Zn of the P element derived from compound A to the Zn element derived from the negative electrode active material is preferably 0.00001 or more and 0.0014 or less, more preferably 0.0001 or more and 0.0008 or less. When P / Zn is 0.00001 or more, the liquid balance between the positive and negative electrodes during low-temperature discharge is easily improved. When P / Zn is 0.0014 or less, good viscosity and ion conductivity are easily obtained in the electrolyte in the negative electrode. The amount of Zn and the amount of P in the negative electrode can be obtained, for example, by ICP emission spectrophotometry.
[0018] As compound A, for example, phosphoric acid can be mentioned. Compound A can be a salt such as an alkali metal salt, for example, a phosphate. As phosphate, for example, potassium phosphate (K 3 PO 4 ), sodium phosphate (Na 3 PO 4 ), potassium hydrogen phosphate (K 2 HPO 4 ), sodium hydrogen phosphate (Na 2 HPO 4 ) etc. Among them, potassium phosphate is preferred. Compound A may be used alone or in combination of two or more.
[0019] In addition, compound A can be an ester compound A having a PO bond (hereinafter, also referred to as ester compound A). Ester compound A has a PO bond-containing group as a hydrophilic group and a hydrocarbon group as a hydrophobic group, and can act as an anionic surfactant. The PO bond-containing group is easily adsorbed on the negative electrode active material. From the viewpoint of hydrophilicity, the PO bond-containing group can have 1 or 2 OM groups (M is a hydrogen atom or an alkali metal atom). Ester compound A can have hydrophilic groups such as polyoxyethylene and polyoxypropylene.
[0020] The ester compound A is preferably a phosphite or a phosphate, and more preferably a phosphate. In this case, it is easy to significantly improve the balance of the electrolyte (water) between the positive and negative electrodes during low-temperature discharge. More specifically, as the ester compound A, polyoxyalkylene alkyl ether phosphate, alkyl phosphate, etc. can be cited. The ester compound A can be a monoester, a diester, or a triester.
[0021] From the viewpoint of improving discharge performance in a low temperature environment, the ester compound A is preferably a monoester compound represented by the following general formula (1). By allowing the compound represented by the general formula (1) to coexist with terephthalic acid at a specific molar ratio, the liquid balance between the positive and negative electrodes during low temperature discharge is easily improved.
[0022]
[0023] In the general formula (1), R 1 It is a hydrocarbon group having 1 to 20 carbon atoms. 1 It is hydrophobic, which improves the balance of the electrolyte (water) between the positive and negative electrodes during low-temperature discharge. 2 For ethylene: -CH 2 CH 2 - or propylene: -CH 2 (CH 3 )CH 2 -. n1 means R 2 The average number of moles of O added (R2 O unit) is 0 or more and 8 or less. When n1=0, R 1 Without the help of (R 2 O) n1 It is bonded to the phosphorus atom via an oxygen atom. 1 is a hydrogen atom or OM 1 Key, M. 1 Y is a hydrogen atom or an alkali metal atom. 1 is a hydrogen atom or an alkali metal atom. Examples of the alkali metal atom include a potassium atom and a sodium atom.
[0024] From the perspective of further improving discharge performance in a low temperature environment, R 1 Preferably, the hydrocarbon group has a carbon number of 2 or more and 16 or less, and more preferably, the hydrocarbon group has a hydrocarbon number of 2 or more and 10 or less. n1 may be 1 or more and 4 or less, preferably 2 or more and 4 or less. In this case, the diffusibility of the electrolyte from the negative electrode to the positive electrode is easily improved, and the liquid balance between the positive and negative electrodes during low-temperature discharge is easily improved.
[0025] From the viewpoint of improving discharge performance in a low temperature environment, the ester compound A is preferably a diester compound represented by the following general formula (2). By allowing the compound represented by the general formula (2) to coexist with terephthalic acid at a specific molar ratio, the liquid balance between the positive and negative electrodes during low temperature discharge is easily improved.
[0026]
[0027] In the general formula (2), R 3 and R 5 Each independently represents a hydrocarbon group having 1 to 20 carbon atoms. 3 and R 5 It is hydrophobic, which improves the balance of the electrolyte (water) between the positive and negative electrodes during low-temperature discharge. 4 and R 6 Each is independently ethylene: -CH 2 CH 2 - or propylene: -CH 2 (CH 3 )CH 2 -. n2 means R 4 The average number of moles of O added (R 4 O unit) is 0 or more and 8 or less. When n2=0, R 3 Without the help of (R 4 O) n2 It is bonded to the phosphorus atom via an oxygen atom. n3 represents OR 6 The average number of added moles (OR 6The average number of repeating units of the unit is 0 or more and 8 or less. When n3=0, R 5 Without the help of (OR 6 ) n3 It is bonded to the phosphorus atom via an oxygen atom. 2 is a hydrogen atom or OM 2 Key, M. 2 It is a hydrogen atom or an alkali metal atom (such as a potassium atom, a sodium atom, etc.).
[0028] From the perspective of further improving discharge performance in a low temperature environment, R 3 and R 5 Each independently preferably has a hydrocarbon group with a carbon number of 2 or more and 16 or less, and more preferably has a hydrocarbon group with a hydrocarbon number of 2 or more and 10 or less. n2 and n3 each independently may be 1 or more and 4 or less. The total of n2 and n3 is preferably 2 or more and 4 or less. In this case, the diffusibility of the electrolyte from the negative electrode to the positive electrode is easily improved, and the liquid balance between the positive and negative electrodes during low-temperature discharge is easily improved.
[0029] R in formula (1) 1 And R in formula (2) 3 and R 5 The hydrocarbon group may be straight-chain or branched. The hydrocarbon group includes alkyl, alkenyl, etc. Among them, the alkyl group having a carbon number of 1 or more and 20 or less is preferred. The alkyl group includes: methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, etc. The alkenyl group includes: vinyl, 1-propenyl, allyl, isopropenyl, 2-butenyl, 3-butenyl, 2-pentenyl, 3-pentenyl, etc.
[0030] The content of terephthalic acid in the negative electrode can be, for example, 0.01 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the negative electrode active material. When the content of terephthalic acid in the negative electrode is 0.01 parts by mass or more per 100 parts by mass of the negative electrode active material, the liquid balance between the positive and negative electrodes during low-temperature discharge is easily improved. When the content of terephthalic acid in the negative electrode is 0.5 parts by mass or less per 100 parts by mass of the negative electrode active material, good viscosity and ion conductivity are easily obtained in the electrolyte in the negative electrode.
[0031] Terephthalic acid is sometimes difficult to dissolve in the electrolyte in the negative electrode and can exist in a particle form. The particle size (D50) of terephthalic acid contained in the negative electrode can be, for example, 25 μm or more and 210 μm or less, or 100 μm or more and 210 μm or less. In this case, the dispersibility of the negative electrode is improved, and the negative electrode is easily homogenized.
[0032] In this specification, the particle size (D50) refers to the median particle size in the volume-based particle size distribution. The particle size (D50) is obtained, for example, using a laser diffraction / scattering particle distribution measuring device.
[0033] Examples of the alkaline dry battery according to one embodiment of the present disclosure include cylindrical batteries and coin batteries.
[0034] Hereinafter, the alkaline dry cell of the present embodiment will be described in detail based on the accompanying drawings. It should be noted that the present disclosure is not limited to the following embodiments. In addition, it can be appropriately changed within the scope of the effect of the present disclosure. Furthermore, it can also be combined with other embodiments.
[0035] Figure 1 This is a front view showing a cross section of the alkaline dry battery in one embodiment of the present disclosure in its horizontal half. Figure 1 An example of a cylindrical battery having an inside-out structure is shown. Figure 1 As shown, the alkaline dry battery comprises a hollow cylindrical positive electrode 2, a gel-like negative electrode 3 disposed in the hollow portion of the positive electrode 2, a separator 4 disposed therebetween, and an electrolyte, which are contained in a bottomed cylindrical battery case 1 which also serves as a positive electrode terminal. An alkaline aqueous solution is used as the electrolyte.
[0036] The positive electrode 2 is arranged in contact with the inner wall of the battery case 1. The positive electrode 2 contains manganese dioxide and an electrolyte. The hollow portion of the positive electrode 2 is filled with a gel-like negative electrode 3 via a separator 4. The negative electrode 3 generally contains an electrolyte and a gelling agent in addition to a negative electrode active material containing zinc, compound A and terephthalic acid.
[0037] The separator 4 is a bottomed cylindrical shape and contains an electrolyte. The separator 4 is composed of a cylindrical separator 4a and a liner 4b. The separator 4a is arranged along the inner surface of the hollow portion of the positive electrode 2 and separates the positive electrode 2 from the negative electrode 3. Therefore, the separator arranged between the positive electrode and the negative electrode refers to the cylindrical separator 4a. The liner 4b is arranged at the bottom of the hollow portion of the positive electrode 2 and separates the negative electrode 3 from the battery case 1.
[0038] The opening of the battery case 1 is sealed by a sealing unit 9. The sealing unit 9 is composed of a resin gasket 5, a negative terminal plate 7 which also serves as a negative terminal, and a negative electrode collector 6. The gasket 5 has an annular thin-walled portion 5a. If the internal pressure of the battery exceeds a specified value, the thin-walled portion 5a breaks and the gas is released to the outside of the battery. The negative electrode collector 6 is inserted into the negative electrode 3. The negative electrode collector 6 has a nail-shaped shape with a head and a main body, the main body is inserted into a through hole provided in the central cylindrical portion of the gasket 5, and the head of the negative electrode collector 6 is welded to the flat portion of the central portion of the negative terminal plate 7. The opening end of the battery case 1 is fastened to the flange portion of the peripheral portion of the negative terminal plate 7 via the outer peripheral end of the gasket 5. The outer surface of the battery case 1 is covered with an exterior label 8.
[0039] In the case of an inside-out structure, in a low temperature environment, the viscosity of the electrolyte increases, and the electrolyte (water) is difficult to move to the periphery of the positive electrode (battery shell side). The liquid balance between the positive and negative electrodes is poor, and it is difficult to effectively use the periphery of the positive electrode, and the discharge performance is easily reduced. Therefore, by including compound A and terephthalic acid in the negative electrode at a specific molar ratio, the liquid balance between the positive and negative electrodes is improved, and the discharge performance in a low temperature environment is significantly improved.
[0040] The following is a detailed description of the alkaline dry battery.
[0041] (negative electrode)
[0042] As the negative electrode active material, zinc, zinc alloy, etc. can be cited. From the viewpoint of corrosion resistance, the zinc alloy can contain at least one selected from the group consisting of indium, bismuth and aluminum. The indium content in the zinc alloy is, for example, 0.01 to 0.1 mass%, and the bismuth content is, for example, 0.003 to 0.02 mass%. The aluminum content in the zinc alloy is, for example, 0.001 to 0.03 mass%. From the viewpoint of corrosion resistance, the proportion of elements other than zinc in the zinc alloy is preferably 0.025 to 0.08 mass%.
[0043] The negative electrode active material is usually used in the form of particles. From the viewpoint of the filling property of the negative electrode and the diffusibility of the electrolyte in the negative electrode, the particle size (D50) of the negative electrode active material particles can be, for example, 100 μm to 200 μm, or 110 μm to 160 μm.
[0044] In addition, the particle size (D50) of the negative electrode active material particles can be 120 μm or less, 75 μm or less, or 40 μm or more and 75 μm or less. When the particle size (D50) of the negative electrode active material particles is 120 μm or less, the reaction efficiency of the negative electrode can be further improved, and the discharge performance in a low temperature environment can be further improved. Preferably, the particle size (D50) of the negative electrode active material particles is 75 μm or less.
[0045] From the viewpoint of improving the reaction efficiency of the negative electrode, the particles of the negative electrode active material contained in the negative electrode may contain 60% by volume or more of particles having a particle size of 75 μm or less.
[0046] The negative electrode can be obtained, for example, by mixing a negative electrode active material, compound A, terephthalic acid, a gelling agent, and an electrolyte. The amount of compound A added is, for example, 0.005 parts by mass or more and 0.45 parts by mass or less per 100 parts by mass of the negative electrode active material. As the gelling agent, a known gelling agent used in the field of alkaline dry batteries can be used without particular limitation, and for example, a water-absorbing polymer can be used. Examples of such a gelling agent include polyacrylic acid and sodium polyacrylate. The amount of the gelling agent added is, for example, 0.5 parts by mass or more and 2.5 parts by mass or less per 100 parts by mass of the negative electrode active material.
[0047] When the negative electrode is prepared, if the ester compound A has a hydrocarbon group with a large number of carbon atoms, the ester compound A may be difficult to dissolve in the electrolyte. In this case, when the negative electrode is prepared, the ester compound A and terephthalic acid are simultaneously included in the electrolyte in advance, so that the ester compound A becomes easy to be uniformly dispersed in the electrolyte, and the stirring of the electrolyte can be suppressed to the minimum required, and the foaming accompanied by the stirring of the electrolyte can be suppressed. When the terephthalic acid is not included in the electrolyte in advance when the negative electrode is prepared, in order to make the ester compound A uniformly dispersed in the electrolyte, the electrolyte must be fully stirred, and the electrolyte may foam.
[0048] In order to improve corrosion resistance, a compound containing a metal with high hydrogen overvoltage such as indium or bismuth may be appropriately added to the negative electrode. In order to suppress the growth of zinc or other dendrites, a small amount of a silicate compound such as silicate or its potassium salt may be appropriately added to the negative electrode.
[0049] (Negative electrode current collector)
[0050] The material of the negative electrode collector inserted into the gelled negative electrode includes, for example, metals and alloys. The negative electrode collector preferably contains copper, and may be made of, for example, an alloy containing copper and zinc, such as brass. The negative electrode collector may be plated with tin plating or the like as needed.
[0051] (positive electrode)
[0052] The positive electrode generally contains a conductive agent and an electrolyte in addition to manganese dioxide as a positive electrode active material. In addition, the positive electrode may further contain a binder as necessary.
[0053] As manganese dioxide, electrolytic manganese dioxide is preferred. Examples of the crystal structure of manganese dioxide include α-type, β-type, γ-type, δ-type, ε-type, η-type, λ-type, and ramsdellite-type.
[0054] The manganese dioxide is used in the form of powder. From the viewpoint of easily ensuring the filling property of the positive electrode and the diffusibility of the electrolyte in the positive electrode, etc., the particle size (D50) of the manganese dioxide is, for example, 25 μm or more and 60 μm or less.
[0055] From the viewpoint of moldability and suppression of positive electrode expansion, the BET specific surface area of manganese dioxide can be, for example, 20 m 2 / g or more and 50m 2 It should be noted that the BET specific surface area refers to the surface area measured and calculated using the BET formula, which is a theoretical formula for multi-molecular layer adsorption. The BET specific surface area can be measured, for example, using a specific surface area measuring device based on a nitrogen adsorption method.
[0056] As the conductive agent, for example, in addition to carbon black such as acetylene black, conductive carbon materials such as graphite can also be cited. As graphite, natural graphite, artificial graphite, etc. can be used. The conductive agent can be fibrous, etc., preferably powdered. The particle size (D50) of the conductive agent is, for example, 3 μm or more and 20 μm or less.
[0057] The content of the conductive agent in the positive electrode is, for example, 3 parts by mass or more and 10 parts by mass or less, and preferably 5 parts by mass or more and 9 parts by mass or less, relative to 100 parts by mass of manganese dioxide.
[0058] The positive electrode can be obtained, for example, by press-molding a positive electrode mixture containing a positive electrode active material, a conductive agent, an alkaline electrolyte, and a binder as required into a pellet shape. The positive electrode mixture can be temporarily formed into a flaky or granular shape, classified as required, and then press-molded into a pellet shape.
[0059] After the pellets are housed in the battery case, they can be pressurized a second time using a predetermined tool so that they are in close contact with the inner wall of the battery case.
[0060] (Separator)
[0061] As the material of the separator, for example, cellulose, polyvinyl alcohol, etc. can be exemplified. The separator can be a non-woven fabric using fibers of the above materials as the main body, or a microporous film such as cellophane, polyolefin, etc. A non-woven fabric and a microporous film can be used in combination. As the non-woven fabric, examples can be given: a non-woven fabric obtained by mixing cellulose fibers and polyvinyl alcohol fibers as the main body, a non-woven fabric obtained by mixing rayon fibers and polyvinyl alcohol fibers as the main body, etc.
[0062] Figure 1In the embodiment, a cylindrical separator 4a and a backing paper 4b are used to form a bottomed cylindrical separator 4. The bottomed cylindrical separator is not limited thereto, and any separator of a known shape used in the field of alkaline dry batteries can be used. The separator can be composed of one sheet, or a plurality of sheets can be overlapped if the sheet constituting the separator is thin. The cylindrical separator can be formed by winding a thin sheet multiple times.
[0063] The thickness of the separator is, for example, 200 μm or more and 300 μm or less. The separator preferably has the above thickness as a whole, and if the sheet constituting the separator is thin, a plurality of sheets may be stacked to achieve the above thickness.
[0064] (Electrolyte)
[0065] The electrolyte is contained in the positive electrode, the negative electrode and the separator. As the electrolyte, for example, an alkaline aqueous solution containing potassium hydroxide is used. The concentration of potassium hydroxide in the electrolyte is, for example, 30% by mass or more and 50% by mass or less. The electrolyte may further contain zinc oxide. The concentration of zinc oxide in the electrolyte is, for example, 1% by mass or more and 5% by mass or less.
[0066] (Battery housing)
[0067] For example, a bottomed cylindrical metal case is used as the battery case. For example, a nickel-plated steel plate is used as the metal case. In order to improve the adhesion between the positive electrode and the battery case, it is preferred to use a battery case in which the inner surface of the metal case is covered with a carbon coating.
[0068] <Example>
[0069] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0070] 《Example 1》
[0071] Follow the steps below to make Figure 1 The shown single 3-size cylindrical alkaline dry cell battery (LR6).
[0072] [Production of positive electrode]
[0073] Graphite powder (particle size (D50) 8 μm) as a conductive agent was added to electrolytic manganese dioxide powder (particle size (D50) 35 μm) as a positive electrode active material to obtain a mixture. The mass ratio of electrolytic manganese dioxide powder to graphite powder was set to 92.4:7.6. It should be noted that the electrolytic manganese dioxide powder used was a specific surface area of 41 m 2 / g. 1.5 parts by mass of electrolyte was added to 100 parts by mass of the mixture, and after sufficient stirring, compression molding was performed into scales to obtain a positive electrode mixture. An alkaline aqueous solution containing potassium hydroxide (concentration 35% by mass) and zinc oxide (concentration 2% by mass) was used as the electrolyte.
[0074] The flaky positive electrode mixture was pulverized into particles, and 11 g of the obtained particles were classified using a 10-100 mesh sieve and press-molded into a predetermined hollow cylindrical shape with an outer diameter of 13.65 mm to prepare two positive electrode pellets.
[0075] [Production of negative electrode]
[0076] The negative electrode active material, the electrolyte, the gelling agent, the compound A and terephthalic acid (particle size (D50) 130 μm) are mixed to obtain a gelled negative electrode 3. The negative electrode active material uses a zinc alloy powder (particle size (D50) 130 μm) containing 0.02 mass% indium, 0.01 mass% bismuth and 0.005 mass% aluminum. The proportion of particles below 75 μm in the zinc alloy powder is 23 volume%. The electrolyte used is the same as the electrolyte used in the preparation of the positive electrode. A mixture of cross-linked branched polyacrylic acid and highly cross-linked chain polyacrylate sodium is used as the gelling agent. Compound A uses potassium phosphate (K 3 PO 4 ). The mass ratio of the negative electrode active material to the electrolyte to the gelling agent is set to 100:50:1.
[0077] The molar ratio of compound A to terephthalic acid was set to 0.28. The content of compound A in the negative electrode was set to 0.05 parts by mass per 100 parts by mass of the negative electrode active material. The molar ratio of P element to Zn element in the negative electrode was set to 0.00015. The content of terephthalic acid in the negative electrode was set to 0.14 parts by mass per 100 parts by mass of the negative electrode active material.
[0078] [Assembly of alkaline dry cell batteries]
[0079] Varniphite manufactured by Nippon Graphite Co., Ltd. is applied to the inner surface of a bottomed cylindrical shell made of nickel-plated steel plate (outer diameter 13.80 mm, wall thickness of the cylindrical part 0.15 mm, height 50.3 mm) to form a carbon coating with a thickness of about 10 μm, thereby obtaining a battery shell 1. After two positive electrode pellets are inserted longitudinally into the battery shell 1, they are pressurized to form a positive electrode 2 in a state of being closely attached to the inner wall of the battery shell 1 via a conductive film 10. After a bottomed cylindrical separator 4 is arranged on the inner side of the positive electrode 2, an electrolyte is injected and impregnated into the separator 4. The electrolyte used is the same as the electrolyte used in the production of the positive electrode. It is left in this state for a predetermined time to allow the electrolyte to penetrate from the separator 4 to the positive electrode 2. Thereafter, 6 g of the gel-like negative electrode 3 is filled into the inner side of the separator 4.
[0080] The separator 4 is composed of a cylindrical separator 4a and a backing paper 4b. The cylindrical separator 4a and the backing paper 4b are made of a nonwoven fabric sheet (weight per unit area 28 g / m2) obtained by mixing rayon fiber and polyvinyl alcohol fiber in a mass ratio of 1:1 as the main component. 2 The thickness of the nonwoven fabric sheet used for the backing paper 4b is 0.27 mm. The separator 4a is formed by rolling up a nonwoven fabric sheet having a thickness of 0.09 mm in three layers.
[0081] The negative electrode collector 6 is obtained as follows: general brass (Cu content: about 65 mass%, Zn content: about 35 mass%) is press-processed into a nail shape, and then the surface is tin-plated. The diameter of the main body of the negative electrode collector 6 is set to 1.15 mm. The head of the negative electrode collector 6 is welded to the negative terminal plate 7 made of nickel-plated steel plate. After that, the main body of the negative electrode collector 6 is pressed into the through hole in the center of the gasket 5 with polyamide 6 and 12 as the main component. In this way, a sealing unit 9 formed by the gasket 5, the negative terminal plate 7 and the negative electrode collector 6 is made.
[0082] Next, the sealing unit 9 is set at the opening of the battery case 1. At this time, the main body of the negative electrode collector 6 is inserted into the negative electrode 3. The opening end of the battery case 1 is fastened to the peripheral edge of the negative electrode terminal plate 7 via the gasket 5, and the opening of the battery case 1 is sealed. The outer surface of the battery case 1 is covered with an external label 8. In this way, the alkaline dry battery A1 is manufactured.
[0083] [evaluate]
[0084] The discharge performance of the battery A1 prepared above in a low-temperature environment was evaluated by the following method.
[0085] The obtained battery was discharged at 250 mA in an environment of 0° C. The discharge time until the closed circuit voltage of the battery reached 0.9 V was measured. The discharge time was expressed as an index with the discharge time of the battery X1 of Comparative Example 1 being 100.
[0086] 《Examples 2 to 5, Comparative Examples 5 to 6》
[0087] Batteries A2 to 5 of Examples 2 to 5 and Batteries X5 to X6 of Comparative Examples 5 to 6 were prepared and evaluated in the same manner as Battery A1 of Example 1 except that the content of Compound A in the negative electrode and the molar ratio of Compound A to terephthalic acid were the values shown in Table 1.
[0088] Comparative Example 1
[0089] A battery X1 of Comparative Example 1 was produced and evaluated in the same manner as the battery A1 of Example 1 except that the negative electrode did not contain both the compound A and terephthalic acid.
[0090] Comparative Example 2
[0091] The negative electrode contained potassium phosphate and did not contain terephthalic acid. The content of potassium phosphate in the negative electrode was 0.1 parts by mass per 100 parts by mass of the negative electrode active material.
[0092] A battery X2 of Comparative Example 2 was prepared and evaluated in the same manner as the battery A1 of Example 1 except for the above.
[0093] 《Comparative Example 3》
[0094] A battery X3 of Comparative Example 3 was prepared and evaluated in the same manner as the battery A1 of Example 1 except that the compound A was not contained in the negative electrode.
[0095] 《Comparative Example 4》
[0096] Battery X4 of Comparative Example 4 was prepared and evaluated in the same manner as Battery A1 of Example 1 except that potassium acetate was contained in the negative electrode instead of Compound A and the content of potassium acetate in the negative electrode was 0.1 parts by mass per 100 parts by mass of the negative electrode active material.
[0097] Table 1 shows the evaluation results.
[0098] [Table 1]
[0099]
[0100] In Batteries A1 to A5 of Examples 1 to 5 in which terephthalic acid and Compound A were contained in a specific molar ratio in the negative electrode, the discharge performance in a low temperature environment was improved.
[0101] In the battery X1 of Comparative Example 1 in which terephthalic acid and compound A were not contained in the negative electrode, the discharge performance in a low temperature environment was reduced. In the battery X2 of Comparative Example 2 in which terephthalic acid was not contained in the negative electrode, the discharge performance in a low temperature environment was reduced. In the battery X3 of Comparative Example 3 in which compound A was not contained in the negative electrode, the discharge performance in a low temperature environment was reduced. In the battery X4 of Comparative Example 4 in which potassium acetate was contained in the negative electrode instead of phosphoric acid, the discharge performance in a low temperature environment was reduced.
[0102] In the battery X5 of Comparative Example 5 in which the molar ratio of potassium phosphate to terephthalic acid was less than 0.025, the liquid balance between the positive and negative electrodes was deteriorated, and the discharge performance in a low-temperature environment was reduced.
[0103] In the battery X6 of Comparative Example 6 in which the molar ratio of potassium phosphate to terephthalic acid exceeded 2.5, the potassium phosphate was excessive, the liquid balance between the positive and negative electrodes deteriorated, and the discharge performance in a low temperature environment decreased.
[0104] 《Examples 6 to 12》
[0105] Compounds a1 to a7 (ester compounds A) shown in Tables 2 and 3 were used as compound A. The content of compound A in the negative electrode was 0.24 parts by mass per 100 parts by mass of the negative electrode active material. The molar ratios of (P / Zn) and (compound A / terephthalic acid) were the values shown in Table 4.
[0106] Batteries B1 to B7 of Examples 6 to 12 were prepared and evaluated in the same manner as the battery A1 of Example 1 except for the above. The evaluation results are shown in Table 4.
[0107] [Table 2]
[0108]
[0109] [Table 3]
[0110]
[0111] [Table 4]
[0112]
[0113] In the batteries B1 to B7 of Examples 6 to 12, in which terephthalic acid and compounds a1 to a7 were contained in the negative electrode at a specific molar ratio, the discharge performance in a low temperature environment was improved. In particular, in the batteries B4 to B7, excellent discharge performance was obtained.
[0114] 《Examples 13 to 15》
[0115] Batteries D1 to D3 of Examples 13 to 15 were prepared and evaluated in the same manner as Batteries A1, B1 and B5 of Examples 1, 6 and 10, except that a zinc alloy powder having a particle size (D50) of 65 μm and containing 72% by volume of particles smaller than 75 μm was used as the negative electrode active material. The evaluation results are shown in Table 5.
[0116] [Table 5]
[0117]
[0118] In the batteries D1 to D3 of Examples 13 to 15, the discharge performance in a low-temperature environment was further improved.
[0119] Industrial Applicability
[0120] The alkaline dry battery of the present disclosure is suitable for use as a power source for, for example, portable audio equipment, electronic games, lights, and the like.
[0121] Description of Reference Numerals
[0122] 1 Battery housing
[0123] 2 Positive electrode
[0124] 3 Negative electrode
[0125] 4 Cylindrical separator with bottom
[0126] 4a Cylindrical separator
[0127] 4b Backing paper
[0128] 5. Gasket
[0129] 5a Thin wall part
[0130] 6 Negative electrode collector
[0131] 7 Negative terminal plate
[0132] 8 Exterior Labels
[0133] 9 Sealing unit
Claims
1. An alkaline dry battery comprising: a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte solution, The negative electrode contains: a negative electrode active material containing zinc, a compound A having a PO bond, and terephthalic acid, The molar ratio of the compound A to the terephthalic acid is 0.025 or more and 2.5 or less; In the negative electrode, a molar ratio P / Zn of the P element derived from the compound A to the Zn element derived from the negative electrode active material is 0.00001 or more and 0.0014 or less; The compound A includes at least one selected from the group consisting of phosphoric acid, phosphates, phosphites and phosphate esters.
2. The alkaline dry battery according to claim 1, wherein The compound A comprises a compound represented by the general formula (1): In the general formula (1), R 1 is a hydrocarbon group having 1 to 20 carbon atoms, R 2 is ethylene or propylene, n1 represents R 2 The average added molar number of O is 0 or more and 8 or less, X 1 is a hydrogen atom or OM 1 Key, M. 1 is a hydrogen atom or an alkali metal atom, Y 1 It is a hydrogen atom or an alkali metal atom.
3. The alkaline dry battery according to claim 2, wherein: In the general formula (1), n1 is 2 or more and 4 or less.
4. The alkaline dry battery according to claim 1, wherein The compound A comprises a compound represented by general formula (2): In the general formula (2), R 3 and R 5 are each independently a hydrocarbon group having 1 to 20 carbon atoms, R 4 and R 6 Each independently represents ethylene or propylene, n2 represents R 4 The average number of moles of O added is 0 or more and 8 or less, and n3 represents OR 6 The average number of added moles is 0 or more and 8 or less, X 2 is a hydrogen atom or OM 2 Key, M. 2 It is a hydrogen atom or an alkali metal atom.
5. The alkaline dry battery according to claim 4, wherein: The total of n2 and n3 in the general formula (2) is 2 or more and 4 or less.
6. The alkaline dry battery according to any one of claims 1 to 5, wherein The particle size D50 of the negative electrode active material particles contained in the negative electrode is 120 μm or less.
7. The alkaline dry battery according to any one of claims 1 to 5, wherein The particle size D50 of the negative electrode active material particles contained in the negative electrode is 75 μm or less.
8. The alkaline dry battery according to any one of claims 1 to 5, wherein The particles of the negative electrode active material contained in the negative electrode include 60% by volume or more of particles having a particle size of 75 μm or less.
Citation Information
Patent Citations
Alkaline dry battery
WO2018066204A1
Alkaline dry battery
CN101366135A
Alkaline dry battery
CN109075314A
